The response of wild bees to tree cover and rural land use is mediated by species' traits. (March 2019) - Hall, Mark A.; Nimmo, Dale G.; Cunningham, Saul A.; Walker, Kenneth; Bennett, Andrew F.
Abstract: Worldwide, bees have an important role in ecosystem function and the provision of ecosystem services through their role as pollinators. The diversity of bee species in rural landscapes is influenced by the type of landscape features present, and by land-use and management practices. A key challenge is to understand and predict how species vary across the landscape; and the role of functional traits in determining compositional patterns. We systematically sampled wild bees in four types of landscape feature – open farmland, scattered farmland trees, roadside vegetation and streamside vegetation – in rural landscapes in southern Australia. Landscapes were selected to represent wooded or non-wooded combinations of these site types (e.g. roadside vegetation with or without trees), embedded in farmland with different land-uses (e.g. cropping, grazing). The species richness and abundance of bees was greater at sites containing little or no tree cover; and the cumulative richness of species was greater for tree-less sites than for those with trees. In contrast, species evenness was greatest in wooded site types, indicating these were less dominated by abundant generalist species. Open farmland and treeless roadsides had greater functional diversity (based on species traits) than wooded site types. Strong species trait associations were more numerous with open parts of the landscape, reflecting the greater functional diversity of open site types. These results suggest that a suite of the extant bee fauna can exploit large-scale transformation from former extensively wooded ecosystems to open agricultural landscapes. However, not all species are able to exploit modified landscapes and may disappear with further loss of wooded vegetation. Trait-based approaches provide insight into how changes in landscape pattern affect the bee fauna. Failure to adequately cater for multiple functional groups of bees across all landscape features could mean a substantial loss in species that rely on more natural cover, thus affecting ecosystem function.